"THE EFFECT OF INDEPENDENT ECONOMIC ACTIVITIES OF THE MUHAMMADIYAH KWALA MADU STABAT ISLAMIC BOARDING SCHOOL FOR STAKEHOLDERS" - Siti Nurhalizah Lubis; Nurlaila; Hendra Harmain; Murdifin Azhar; M.Lathief Nasution; Sharifah Norhaliza; Muammar Khadafi (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
Islamic boarding schools, known as Pondok Pesantren, are the oldest educational institutions in Indonesia. Besides their educational role, Pondok Pesantren also play a significant role in the economy due because of their large number with, 37.000 islamic boarding school in total and 4.8 million students across various regions. This substantial economic potential should be harnessed through self-sustaining economic activities, such as those carried out by Pondok Pesantren Muhammadiyah Kwala Madu Stabat. This particular pesantren has engaged in independent economic activities by establishing a corporation that independently produces bottled mineral water. The purpose of this study is to investigate the impact of these self-sustaining economic activities at Pondok Pesantren Muhammadiyah Kwala Madu Stabat on its stakeholders. The method employed involved economic empowerment of the pesantren through workshops with a knowledge and insight transfer approach. The results of the study indicate that the self-sustaining economic activities at Pondok Pesantren Muhammadiyah Kwala Madu Stabat have had a significant impact on its stakeholders. Evidence of this impact includes increased economic inclusion and economic circulation in the surrounding environment of Pondok Pesantren Muhammadiyah Kwala Madu Stabat.